EVALUATION OF INTERNAL CONTROL OF RAW MATERIAL INVENTORY ON FAST FOOD RESTAURANT IN MADURA - Akhmad Fauzan Abrory; Devi Lestari Pramita Putri; Runik Puji Rahayu (Digital Business and Entrepreneurship Journal, 2026)
Fast food businesses need to implement a series of inventory control policies that monitor and determine the level of raw material inventory needed to ensure proper management and avoid disruption to the company's operations. The objectives of this research include: 1. to determine the results of implementing an internal control system for raw material inventory; 2. to determine whether the internal control system is running well or not. The research object was carried out at one of thefast food restaurant in Madura, namely M2M Pamekasan Branch. The type of research is qualitative with a descriptive approach. Data sources are primary and secondary data. Data collection techniques through structured interviews. Data analysis techniques include: data collection, data analysis, data evaluation to drawing conclusions. The results of the study show: 1. The internal control system for raw material inventory implemented by the company includes: a. control environment that includes the attitudes of management and employees towards the importance of control in the company; b. risk assessments carried out by company management must be able to identify various risks faced by the company; c. control procedures which are various processes of efforts carried out by company management to enforce supervision/control of company operations; 2. With the implementation of the internal control system for raw material inventory, it greatly helps the company in ordering raw materials, checking until receiving goods from the head office, everything runs well and smoothly.